Filosofi Pendidikan Ekopedagogi dalam Pembelajaran Sastra: Membangun Kesadaran Lingkungan Mahasiswa Melalui Puisi Theoresia Rumthe - Wa Mirna (EDU-KATA, 2026)
This study aims to describe the values ​​of ecopedagogy education philosophy contained in the poems by Theoresia Rumthe in her book "Mungkin Rumah Tak membawamu Pulang" and describe the implementation of ecopedagogy-based literature learning in building environmental awareness of Indonesian Language Education students at UIN A.M. Sangadji Ambon. This study uses a qualitative approach with a descriptive interpretive research type. The research data are in the form of words, phrases, lines, and stanzas in five poems by Theoresia Rumthe that contain ecopedagogy values. Data collection was carried out through library research, reading, and note-taking techniques. Data analysis used Greg Misiaszek's ecocritical-Freirean approach combined with Moacir Gadotti's ecopedagogy theory and Paulo Freire's critical pedagogy. The results of the study show that Theoresia Rumthe's poems contain values ​​of ecological awareness, human-nature relations, criticism of environmental damage, ecological sustainability, as well as ecological reflective and spiritual dimensions. These values ​​are reflected in ecological symbols such as land, sea, trees, sun, ponds, and plants, which represent the harmonious relationship between humans and the environment. Furthermore, the implementation of ecopedagogy-based literature learning through these poems fosters students' environmental awareness through dialogue, reflection, and contextualization. Literature learning not only enhances the poetry appreciation skills of Indonesian Language Education students at UIN A.M. Sangadji Ambon, but also fosters environmental awareness, ecological awareness, and critical thinking toward ecological issues and environmental sustainability in their surroundings.